68 Implantable cardioverter-defibrillator deactivation in the community: the perspective of palliative care professionals. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Ross, Joy; Hodson, Fiona; Barton, Carys; DeCourcey, Julia; McDonagh, Theresa; Beattie, James
Abstract : Background: Implantable cardioverter defibrillators (ICDs) are increasingly used for prevention of sudden death in people with heart failure (HF). Palliative Care health care professionals (PC-HCP) are increasingly caring for patients approaching end-of-life due to progressive HF or comorbidities. Conversations with patients, families and professionals to facilitate ICD deactivation can be challenging, particularly in community versus hospital settings. Method: A survey of PC-HCP was undertaken. Invitations to participate were emailed to hospital and community palliative care teams across the UK. We examined ease of access to appropriate services/personnel from different settings, clarification of whether policies and lines of responsibility were in place, clinical triggers to prompt ICD deactivation and availability of training for staff. Results: 97 HCP responded, of whom 46% were in post >10 years. 59% had cared for <5 patients, 16% 5–10 patients and 3 >30 patients with ICDs in the previous 12 mths. Similar numbers worked in NHS or independent sectors (38% each), 24% working across both. 27% were based in primary/community care, 36% secondary care and 37% across both settings. 26% participated in multidisciplinary HF meetings and 72% of these had presented cases for consideration of ICD deactivation. 60% were aware of a site-specific ICD deactivation protocol in their workplace, with less knowledge about linking to a regional or DNACPR protocols or ReSPECT process. Where protocols were in place, 42% contained specific guidance for community-based deactivation. Delays in deactivation were limited by staff resource/availability in both community and hospital settings, particularly out of hours, with only 36% feeling that appropriately trained staff and equipment were available out of hours. Prompt access to a magnet for emergency deactivation differed across settings: hospital (62%), hospice (72%), home (33%) and Care Home (22%). Less than half (43%) agreed that PC-HCP had adequate training to facilitate use of the magnet. Conclusion: PC-HCP report significant barriers to ICD deactivation, particularly in the community. Local and regional policy still needs to be standardised across the UK, and education and training provided to enable timely conversations and integrated pathways in place. Further analysis of case vignettes will be presented.